Treatment technologies to mitigate the harmful effects of recalcitrant fluoroquinolone antibiotics on the environ- ment and human health. (15th December 2021) - Mathur, Purvi; Sanyal, Doyeli; Callahan, Damien L.; Conlan, Xavier A.; Pfeffer, Frederick M.
Abstract: Antibiotic proliferation in the environment and their persistent nature is an issue of global concern as they induce antibiotic resistance threatening both human health and the ecosystem. Antibiotics have therefore been categorized as emerging pollutants. Fluoroquinolone (FQs) antibiotics are an emerging class of contaminants that are used extensively in human and veterinary medicine. The recalcitrant nature of fluoroquinolones has led to their presence in wastewater, effluents and water bodies. Even at a low concentration, FQs can stimulate antibacterial resistance. The main sources of FQ contamination include waste from pharmaceutical manufacturing industries, hospitals and households that ultimately reaches the wastewater treatment plants (WWTPs). The conventional WWTPs are unable to completely remove FQs due to their chemical stability. Therefore, the development and implementation of more efficient, economical, convenient treatment and removal technologies are needed to adequately address the issue. This review provides an overview of the technologies available for the removal of fluoroquinolone antibiotics from wastewater including adsorptive removal, advanced oxidation processes, removal using non-carbon based nanomaterials, microbial degradation and enzymatic degradation. Each treatment technology is discussed on its merits and limitations and a comparative view is presented on the choice of an advanced treatment process for future studies and implementation. A discussion on the commercialization potential and eco-friendliness of each technology is also included in the review. The importance of metabolite identification and their residual toxicity determination has been emphasized. The last section of the review provides an overview of the policy interventions and regulatory frameworks that aid in retrofitting antibiotics as a central key focus contaminant and thereby defining the discharge limits for antibiotics and establishing safe manufacturing practices. Graphical abstract: Image 1 Highlights: Advanced technologies to remove antibiotic residues from environment is reviewed. Metabolites and importance of studying their residual toxicity is emphasized. Modelling approach to establish PNEC as ETP discharge limit has been discussed. Policy interventions needed to control unmonitored antibiotic release is discussed.